2014
DOI: 10.3988/jcn.2014.10.3.229
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Brain Activity Changes in Patients with Migraine: A Short-Term Longitudinal Study

Abstract: Background and PurposeWhether or not migraine can cause cumulative brain alterations due to frequent migraine-related nociceptive input in patients is largely unclear. The aim of this study was to characterize longitudinal changes in brain activity between repeated observations within a short time interval in a group of female migraine patients, using resting-state functional magnetic resonance imaging.MethodsNineteen patients and 20 healthy controls (HC) participated in the study. Regional homogeneity (ReHo) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 26 publications
6
33
0
Order By: Relevance
“…These findings support the idea of dynamically changing functional connectivity during migraine cycle, similarly to an earlier longitudinal resting state fMRI study [6]. …”
Section: Discussionsupporting
confidence: 89%
“…These findings support the idea of dynamically changing functional connectivity during migraine cycle, similarly to an earlier longitudinal resting state fMRI study [6]. …”
Section: Discussionsupporting
confidence: 89%
“…If one presumes that brain structure and function change as a result of recurrent migraine attacks, this finding is easy to accept—in general, the longer a person has had migraine, the more attacks they have had, and the greater the brain changes. In support of the notion that recurrent migraine attacks alter brain function, a single longitudinal study of 19 migraine patients who had increasing headache activity over 6 weeks demonstrated correlations between changes in functional connectivity and the worsening clinical pattern . However, it is not definitively known if brain structure changes are a result of recurrent migraine attacks or if the extent of brain structure abnormality correlates with age of onset for migraine—eg, the more abnormal brain structure is, the younger age of onset for migraine, and/or the younger brain is more susceptible to the effects of migraine.…”
Section: Discussionmentioning
confidence: 99%
“…[34,44,45] A novel finding in the present study was the lower baseline ReHo of the MTG was associated with greater pain relief (ΔVAS) after the PRT procedure. The result indicates that the pre-surgical ReHo values in this area can be used as neuroimaging markers for predicting response to the treatment.…”
Section: Discussionmentioning
confidence: 76%